Cost-effectiveness analysis of a pragmatic randomized trial evaluating surgical reconstruction versus rehabilitation in patients with long-standing anterior cruciate ligament injury - Leal, J; Mirza, B; Davies, L; Fletcher, H; Stokes, J; Cook, JA; Price, A; Beard, DJ (British Editorial Society of Bone and Joint Surgery, 2024)
Aims The aim of this study was to estimate the incremental use of resources, costs, and quality of life outcomes associated with surgical reconstruction compared to rehabilitation for long-standing anterior cruciate ligament (ACL) injury in the NHS, and to estimate its cost-effectiveness. Methods A total of 316 patients were recruited and randomly assigned to either surgical reconstruction or rehabilitation (physiotherapy but with subsequent reconstruction permitted if instability persisted after treatment). Healthcare resource use and health-related quality of life data (EuroQol five-dimension five-level health questionnaire) were collected in the trial at six, 12, and 18 months using self-reported questionnaires and medical records. Using intention-to-treat analysis, differences in costs, and quality-adjusted life years (QALYs) between treatment arms were estimated adjusting for baseline differences and following multiple imputation of missing data. The incremental cost-effectiveness ratio (ICER) was estimated as the difference in costs divided by the difference in QALYs between reconstruction and rehabilitation. Results At 18 months, patients in the surgical reconstruction arm reported higher QALYs (0.052 (95% confidence interval (CI) -0.012 to 0.117); p = 0.177) and higher NHS costs (£1,017 (95% CI 557 to 1,476); p < 0.001) compared to rehabilitation. This resulted in an ICER of £19,346 per QALY with the probability of surgical reconstruction being cost-effective of 51% and 72% at a willingness-to-pay threshold of £20,000 and £30,000 per QALY, respectively. Conclusion Surgical reconstruction as a management strategy for patients with long-standing ACL injury is more effective, but more expensive, at 18 months compared to rehabilitation management. In the UK setting, surgical reconstruction is cost-effective.